A Partially Fluorinated Three‐fold Interpenetrated Stable Metal‐Organic Framework with Selective CO2 Uptake12. Issue 6 (12th February 2014) - Santra, Atanu; Lah, Myoung Soo; Bharadwaj, Parimal K.
Abstract The hydrothermal reaction of Zn(NO3)2·H2O and a linear 2, 2′‐bis‐trifluoromethyl‐biphenyl‐4, 4′‐dicarboxylic acid (H2L) ligand with –CF3 groups at each phenyl moiety of the biphenyl rings leads to the formation of a three‐fold interpenetrated metal‐organic framework (MOF), {[Zn2.66O0.66(L)2]·2H2O}n (1) at 180 °C. Single‐crystal X‐ray diffraction studies revealed that 1 is constructed from polynuclear clusters [Zn4O(COO)6] as secondary building units (SBU). These SBU are connected through the L2– to generate an overall three‐dimensional structure with a 6‐connected primitive cuboidal (α‐Po) network. Thermogravimetric analyses and variable temperature powder X‐ray diffraction measurements suggested that 1 is thermally stable. The porosity of 1 was estimated by N2, CO2, H2, and CH4 at different temperatures. The framework showed high selectivity of CO2 uptake over N2 and CH4. Furthermore, solid‐state photoluminescence studies were carried out for complex 1 upon excitation at 275 nm at room temperature.